Association between fat mass through adolescence and arterial stiffness: a population-based study from The Avon Longitudinal Study of Parents and Children. (July 2019) - Dangardt, Frida; Charakida, Marietta; Georgiopoulos, Georgios; Chiesa, Scott T; Rapala, Alicja; Wade, Kaitlin H; Hughes, Alun D; Timpson, Nicholas J; Pateras, Konstantinos; Finer, Nick; Sattar, Naveed; Davey Smith, George; et al.
Summary: Background: The link between adiposity, metabolic abnormalities, and arterial disease progression in children and adolescents remains poorly defined. We aimed to assess whether persistent high adiposity levels are associated with increased arterial stiffness in adolescence and any mediation effects by common metabolic risk factors. Methods: We included participants from the Avon Longitudinal Study of Parents and Children (ALSPAC) who had detailed adiposity measurements between the ages 9–17 years and arterial stiffness (carotid to femoral pulse wave velocity [PWV]) measured at age 17 years. Body-mass index (BMI) and waist-to-height ratio were calculated from weight, height, and waist circumference measurements whereas fat mass was assessed using repeated dual-energy x-ray absorptiometry (DEXA) scans. We used total and trunk fat mass indices (FMIs) to classify participants as normal (<75th percentile) or high (>75th percentile) FMI. We classified participants as being metabolically unhealthy if they had three or more of the following risk factors: high levels of systolic blood pressure, triglycerides, or glucose (all >75th percentile) or low levels of high-density lipoprotein (<25th percentile). We used multivariable linear regression analysis to assess the relationship between PWV and exposure to adiposity, and tested for linear trend of PVW levels across ordinal groups. We used latent class growth mixture modelling analysis to assess the effect of longitudinal changes in adiposity indices through adolescence on arterial stiffness. Findings: We studied 3423 participants (1866 [54·5%] female and 1557 [45·5%] male). Total fat mass was positively associated with PWV at age 17 years (0·004 m/s per kg, 95% CI 0·001–0·006; p=0·0081). Persistently high total FMI and trunk FMI between ages 9 and 17 years were related to greater PWV (0·15 m/s per kg/m 2, 0·05–0·24; p=0·0044 and 0·15 m/s per kg/m 2, 0·06–0·25; p=0·0021) compared with lower FMI. Metabolic abnormalities amplified the adverse effect of high total FMI on arterial stiffness (PWV 6·0 m/s [95% CI 5·9–6·0] for metabolically healthy participants and 6·2 m/s [5·9–6·4] for metabolically unhealthy participants). Participants who restored normal total FMI in adolescence (PWV 5·8 m/s [5·7–5·9] for metabolically healthy and 5·9 m/s [5·6–6·1] for metabolically unhealthy) had comparable PWV to those who had normal FMI throughout (5·7 m/s [5·7–5·8] for metabolically healthy and 5·9 m/s [5·8–5·9] for metabolically unhealthy). Interpretation: Persistently high fat mass during adolescence was associated with greater arterial stiffness and was further aggravated by an unfavourable metabolic profile. Reverting to normal FMI in adolescence was associated with normal PWV, suggesting adolescence as an important period for interventions to tackle obesity in the young to maximise long-term vascular health. Funding: UK Medical Research Council, Wellcome Trust, British Heart Foundation, and AFA Insurances